An Application of Artificial Intelligence to Support the Discovering of Roman Centuriation Remains - Pietro Fusco; Salvatore Venticinque; Rocco Aversa (IEEE Access, 2022)
Archaeological research that uncovers ancient artifacts is of critical importance, since ruins and objects are the only way to deal with the history of a city. Artificial intelligence techniques can support the archaeologists to discover remains which are difficult to be identified manually as they must be sought on a vast territory or because they are hidden from direct observation. Here we present an original methodology that integrates deep learning and computer vision techniques to identify, from aerial pictures, remains of the Centuriation, that is an ancient Roman system for the division of the territory.